Influence of Dosed Cryoeffect on Reparative Process in Thyroid Gland after Surgical Treatment of Diffusive Toxic Goiter (Ultra Sound Examination Data) - Makedonskaya, V. A.; Khaziev, V. V.; Tyazhelova, O. V. (Problems of Cryobiology and Cryomedicine, 2006)
Demonstrated data of thyroid gland ustrasond examination within a post-operative period in patients with diffusive toxic goiter after surgical treatment with applying intraoperative local dosed cryoeffect on thyroid gland shank testify to normalisation of this gland tissue echostructure following 1 year after operation with hyperplasia and autoimmune regression slow rates.